The retro writing of history: "Artigas Blues Band" by Amir Hamed (Anclajes, 2017)
The rise of the historical novel left its mark in the literary field of the democratic opening of Uruguay while being a way of exploring the causes of State terror during the last dictatorship (1973-1985). This was a major concern among the generation of 1960s and 1970s, who were formed in the heat of revolutionary fervor and later suffered under the dictatorial context. This article seeks to analyze Amir Hamed’s Artigas Blues Band (1994) as a strong detour from those historical novels of post-dictatorship. Although Hamed grew up in dictatorship, he belongs to the generation emerging in democracy. He does not rewrite the past to question its historical failures but instead retrowrites it to construct a place from which to do away with the past, the “Switzerland of America”, of the left’s promises, of the legacies of dictatorship, to violently stir the grey democracy with celebration, desire, humor, music, creativity, the new, the young, the other.
Keywords: Amir Hamed; Uruguayan literature; 20th century; literary critique; Uruguay